Appendiceal Intussusception - S. S. Maskin; N. I. Fetisov; V. V. Matyukhin; C. Yuan (Неотложная медицинская помощь, 2021)
The pathology of the appendix remains one of the topical areas of abdominal surgery. Its rare diseases can be difficult to diagnose and treat, and are accompanied by the development of serious complications. One of them is  intussusception of the appendix to the cecum. Intussusception can be caused by previously undiagnosed primary lesions of the appendix. At the same time, it can simulate tumor and tumor-like formations of the cecum and lead to  diagnostic errors. The literature review provides modern data on the history of the study of the problem, the epidemiology of classification, the causes and mechanisms of the development of appendiceal intussusception, the methods of its diagnosis and treatment.